USAGE OF INFORMATION AND PEDAGOGICAL TECHNOLOGIES IN DISTANCE LEARNING AND THE TEACHING OF FOREIGN LANGUAGES - Sultonova Durdonakhon Shuhratjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Teaching students how to function independently in the information- educational environment that is growing everyday and how to use the flow of information intelligently is one of the objectives of today's educational process, as addressed in this article.